Investigation On Waste Management And Its Recycling - Kuldeep Soni; Gaurav Mittal; Garv Jain; Ashish Laddha (International Journal of Pollution: Prevention & Control, 2025)
For doing the inventions with the Green Initiatives recycling and reusing of products is very essential. It has been acknowledged that one of the most important elements in achieving growth, environmental sustainability, and improved quality of life is green product innovation. Theory and practice have made it a strategic priority to comprehend how innovation and sustainability combine to produce green product innovation. In the face of growing environmental concerns and resource depletion, the implementation of effective recycling and reuse strategies has become imperative for achieving sustainable waste management practices. This research paper presents a comprehensive review of the present state of recycling and reuse initiatives, aiming to highlight their significance in conserving natural resources.In this research paper we will discuss some schemes and all the practices for recycling and reusing of various materials and the importance of doing innovations with Green Initiatives.The paper begins by examining the fundamental concepts of recycling and reusing of materials, including their definitions, their principles, benefits and importance of it. Then it goes into a depth of various methods, techniques and different technologies which handle mechanical recycling, chemical recycling, biological recycling and reusing of materials processes. Further the paper investigates and discusses the various barriers and challenges during this process.In conclusion, this research paper underscores the critical role of recycling and reuse in advancing the goals of sustainable development and environmental stewardship. By elucidating the multifaceted benefits, challenges, and opportunities associated with recycling and reuse, it seeks to inform policyheads, industries stakeholders, and the broader community about the importance of transitioning towards a circular economy paradigm.
Keywords: Reuse; Sustainability; economy; employment; recycle